A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia - Łagowska, Bozena; Martin, Jon H.; Hodgson, Chris J. (Zootaxa, 2017)
The adult female, first-instar nymph, second-instar male, third-instar female, pupa and adult male of a new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia, M. ulubendulensis Łagowska & Martin sp. n., are described and illustrated, while the second-instar female is only described. Marsipococcus is rediagnosed and a key to the adult females of the four species now placed in this genus is included.